Impact of Diabetes Mellitus on Renal transplant outcome - Muhammad Tanzeel Abbasi; Mariam Arif; Nayyar Saleem (Archives of Clinical Nephrology - Peertechz Publications, 2021)
Diabetes Mellitus (DM) is a potent risk factor for post-transplant cardiovascular complications and infections. Management of diabetes and its complications in renal transplant recipients is a challenging task. This is a frequently encountered predicament in transplant setups. An erratic glycemic control during dialysis is a predictor of poor graft and patient outcomes after kidney transplantation.  Literature review reveals majority studies explaining post-transplant diabetes and its role in graft and patient survival. However, a wide range of opinion exists about the impact of pre-transplant DM on transplant outcomes. Measurement of HbA1c levels is a significant tool for assessment of glycemic control. A target HbA1c level of <7% is recommended for diabetic patients irrespective of presence or absence of Chronic Kidney Disease (CKD). However, diabetic patients with CKD are at risk of hypoglycemia owing to decreased insulin metabolism so it is safe to keep HbA1c levels between 7-8% in this population. Immunosuppressive medications have a strong contributory role in deterioration of glycemic control. So, it is imperative to achieve strict pre-transplant diabetes control in order to avoid post-transplant complications. Post-transplant diabetes mellitus (PTDM) has been a subject of a large number of trials and is not only considered a serious metabolic complication but also a predisposing factor of diabetic nephropathy in transplanted kidney.